Venômica e antivenômica de Bothrops erythromelas : estudo da variação intraespecífica - Jorge, Roberta Jeane Bezerra (2015)
ABSTRACT Bothrops erythromelas snake is a species of medical importance responsible for snakebites, predominantly in the Northeast of B razil. This study aimed to conduct a comparative proteomic study of venoms pool of this species from five geographical regions of the Northeast: Ceará, Pernambuco, Juazeiro, Paraíba and Itaparica Island. In addition, we investigated the ability of Bothrops antivenom (SAB) of the Vital Brazil Institute and polyspecific serum (BCL) of Costa Rica to neutralize the venoms from these populations (antivenomics) and the ability to neutralize the in vivo haemorrhagic activity of venom. Two - dimensional electrophores is (2DE) showed similar patterns of protein distributed in the range of 14 - 95 kDa molecular mass and isoelectric points ranging from 4 to 8.5. Thirty to forty fractions were collected by Reversed Phase High Performance Liquid Chromatography (RP - HPLC). Each chromatographic fraction collected manually were analyzed by polyacrylamide gel electrophoresis - SDS (SDS - PAGE) and protein bands were excised and subjected to venomic analysis resulting in the identification of approximately 65 proteins and 8 species of peptides belonging to 12 protein families (Bradykinin - Potentiating Peptides (BPPs), Snake Venom Vascular Endothelial Growth Factor (svVEGF), Phospholipase A 2 , Serine Preotease, Metalloproteases class I and class III (PI and PIII - Symp), Disintegrins and Disintegrin - like and Rich in Cysteine domains, C - type Lectins, Nucleotidases (5' - nucleotidase; 5'NT and Phosphodiesterase; PDE), Secretory Proteins rich in Cysteine (CRISP) and snake venoms Phospholipase B. Through this work it was shown that the proteomes of venoms of B. erythromelas of different regions of Northeast are similar and seem to be quite kept according to their geographical distribution, although they contain peculiar differences such as the presence of CRISP detected only in the venoms of Pern ambuco and 5 'NT in the population of Juazeiro; and PDEs only in proteomes of populations of Ceará and Pernambuco and PLB in Ceará, Juazeiro and Itaparica Island. The antivenomics results showed that SAB pentavalent serum immunoreactivity is similar across the five populations and more efficient compared to the polyvalent BCL. However, it can be seen that especially low molecular weight fractions are not efficiently recognized by both antivenoms. Although differences were shown in their neutralization effic acy, both were effective in neutralizing antivenom hemorrhagic activity. Despite the B.erythromelas snake inhabit acomprehensivegeographical area , the five populations showed similar composition, displaying a highly conserved profile of representative venom protein classes. Therefore, this study assigned all proteins in the venom of B. erythromelas that have been characterized in the literature (BPP, PLA2 Asp49, PIII - Symp and svVEGF) and provided additional information to the presence of Serine Proteases and C - type Lectins and other minor or specific components (PDE, 5'NT, PLB, CRISP).